Cetuximab delivery and antitumor effects are enhanced by mild hyperthermia in a xenograft mouse model of pancreatic cancer. Issue 4 (4th March 2016) - Miyamoto, Ryoichi; Oda, Tatsuya; Hashimoto, Shinji; Kurokawa, Tomohiro; Inagaki, Yuki; Shimomura, Osamu; Ohara, Yusuke; Yamada, Keiichi; Akashi, Yoshimasa; Enomoto, Tsuyoshi; Kishimoto, Mikio; Yanagihara, Hideto; et al.
Abstract : Even with current promising antitumor antibodies, their antitumor effects on stroma‐rich solid cancers have been insufficient. We used mild hyperthermia with the intent of improving drug delivery by breaking the stromal barrier. Here, we provide preclinical evidence of cetuximab + mild hyperthermia therapy. We used four in vivo pancreatic cancer xenograft mouse models with different stroma amounts (scarce, MIAPaCa‐2; moderate, BxPC‐3; and abundant, Capan‐1 and Ope‐xeno). Cetuximab (1 mg/kg) was given systemically, and the mouse leg tumors were concurrently heated using a water bath method for 30 min at three different temperatures, 25°C (control), 37°C (intra‐abdominal organ level), or 41°C (mild hyperthermia) ( n = 4, each group). The evaluated variables were the antitumor effects, represented by tumor volume, and in vivo cetuximab accumulation, indirectly quantified by the immunohistochemical fluorescence intensity value/cell using antibodies against human IgG Fc. At 25°C, the antitumor effects were sufficient, with a cetuximab accumulation value (florescence intensity/cell) of 1632, in the MIAPaCa‐2 model, moderate (1063) in the BxPC‐3 model, and negative in the Capan‐1 and Ope‐xeno models (760, 461). By applying 37°C or 41°C heat, antitumor effects were enhanced shown in decreased tumor volumes. These enhanced effects were accompanied by boosted cetuximab accumulation, which increased by 2.8‐fold (2980, 3015) in the BxPC‐3 model, 2.5‐ or 4.8‐fold (1881, 3615) in the Capan‐1 model, and 3.2‐ or 4.2‐fold (1469, 1922) in the Ope‐xeno model, respectively. Cetuximab was effective in treating even stroma‐rich and k‐ras mutant pancreatic cancer mouse models when the drug delivery was improved by combination with mild hyperthermia. Abstract : The present study indicate that cetuximab accumulation and the resulting antitumor effects are enhanced by treatment at 41°C compared to 37°C, especially in the stroma‐rich Capan‐1 Cell‐xeno and Ope‐xeno models.